PENGARUH KUALITAS LABA TERHADAP NILAI PERUSAHAAN MANUFAKTUR - Setiyono, Taufiq Andre; Izzaty, Khairina Nur (Applied Research in Management and Business, 2025)
High quality of earnings can be determine company value. This study aims to determine the effect of quality of earnings (which is includes the cash conversion ratio, operational profit margin, net profit margin, and price-to-earnings ratio) on the manufacturing company value at companies listed on Indonesia Stock Exchange (IDX) for the 2022-2024 period. The population in this study were manufacturing companies listed on the IDX, and 68 sample were selected using a purposive sampling method. Data were analyzed using multiple linear regression analysis with SPSS program. The results showed that the cash conversion ratio, net profit margin, and price-to-earnings ratio had a positive effect on company value, while operational profit margin had no significant effect.